2015
DOI: 10.1248/cpb.c14-00839
|View full text |Cite
|
Sign up to set email alerts
|

Geranylated Flavanones from <i>Paulownia coreana</i> and Their Inhibitory Effects on Nitric Oxide Production

Abstract: The activity-guided fractionation of the MeOH extract of the flower of Paulownia coreana led to the isolation of a new geranylated flavanone, 3′-O-methyl-5′-hydroxydiplacol (1), along with 10 known compounds (2-11). Their structures were determined using spectroscopic techniques, which included one and two dimensional (1-and 2D)-NMR. Among the isolates, compounds 1-6 showed potent inhibitory activities against lipopolysaccharide (LPS)-induced nitric oxide production with IC 50 values ranging 1.48 to 16.66 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Its effects are even better than those of indomethacin, which has been used as a positive control [ 165 ]. It inhibits the production of NO in LPS-stimulated macrophages [ 173 ], and two independent studies showed that diplacone affects the expression of COX-2 [ 167 ] and its activity. Moreover, it was found to be a potent 5-LOX inhibitor [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effects are even better than those of indomethacin, which has been used as a positive control [ 165 ]. It inhibits the production of NO in LPS-stimulated macrophages [ 173 ], and two independent studies showed that diplacone affects the expression of COX-2 [ 167 ] and its activity. Moreover, it was found to be a potent 5-LOX inhibitor [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…IC 50 = 7.2 µM in THP-1 cells [232]. Inhibition of LPS-induced NO production in RAW 264.7 cells, IC 50 = 5.9 µM [173].…”
Section: -O-methyldiplacolmentioning
confidence: 99%
“…Epidemiological studies revealed that an increased daily intake of phenolic compounds in dietary supplements act as anti-oxidant and anti-inflammatory agents to increase thermogenesis and energy expenditure while decreasing inflammation and oxidative stress, further supporting progress towards decreased metabolic disorders [ 1 , 5 ]. Previous studies confirmed that the species of the genus Paulownia (belonging to the family scrophulariaceae) exhibited a broad spectrum of biological effects, including antioxidant, anticarcinogenic [ 6 , 7 ], antiphlogistic [ 8 ], antiviral [ 9 ], antimicrobial [ 10 ] and anti-cholinesterase activities [ 11 ]. Paulownia fortunei (Seem.)…”
Section: Introductionmentioning
confidence: 99%